THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND INTRINSIC MOTIVATION ON STUDENT ACADEMIC ACHIEVEMENT WITH DIFFERENTIATED LEARNING AS A MODERATION VARIABLE AT UPT SMPN IN BANGKALA DISTRICT, JENEPONTO REGENCY - NURFAUZIAH KASMIN; Najamuddin; Dalilul Falihin; Muhammad Rasyid Ridha; Hasruddin Nur (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of emotional intelligence, intrinsic motivation, and differentiated instruction on students’ academic achievement, as well as to examine the moderating role of differentiated instruction among students of UPT SMPN in Bangkala District, Jeneponto Regency. The background of this research arises from the persistent issue of low academic performance, which is presumed to be associated with students’ emotional competence, learning motivation, and the implementation of instructional practices that have not fully accommodated diverse learning needs. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4.The results indicate that emotional intelligence has a positive and significant effect on academic achievement. Intrinsic motivation also demonstrates a positive and significant influence on students’ academic performance. Furthermore, differentiated instruction significantly affects academic achievement, suggesting that instructional strategies tailored to students’ readiness, interests, and learning profiles contribute toimproved learning outcomes. The moderation analysis shows that differentiated instruction strengthens the relationship between emotional intelligence and academic achievement; however, it does not moderate the effect of intrinsic motivation on academic achievement. Overall, this study affirms the importance of enhancing students’ emotional competence, fostering intrinsic motivation, and implementing differentiated instruction to improve academic performance at the junior secondary level. These findings provide valuable implications for teachers, schools, and policymakers in designing more adaptive and student-centered instructional practices.